Effects of a Least-to-Most Prompting Procedure on Multisymbol Message Production in Children With Autism Spectrum Disorder Who Use Augmentative and Alternative Communication - Finke, Erinn H.; Davis, Jennifer M.; Benedict, Morgan; Goga, Lauren; Kelly, Jennifer; Palumbo, Lauren; Peart, Tanika; Waters, Samantha (American journal of speech-language pathology, 2017)
In this study, we investigated the efficacy of a least-to-most (LTM) prompting procedure (Ault & Griffen, 2013; MacDuff, Krantz, & McClannahan, 2001; Neitzel & Wolery, 2009) for increasing use of multisymbol messages in school-age children with autism spectrum disorder (ASD) who use augmentative and alternative communication (AAC) during a storybook reading activity. In the study, we used a single-subject, multiple-probe research design across participants (Kazdin, 1982) with 6 children (ages 8-12) with ASD and who used AAC systems for communication. There were 4 phases in this investigation: (a) baseline, (b) intervention, (c) generalization, and (d) maintenance. All participants exhibited a positive increase in multisymbol message production almost immediately upon introduction of the LTM prompting procedure. The results of the investigation contribute important information on the efficacy of the LTM prompting procedure for teaching use of multisymbol messages to school-age children with ASD who use AAC.